2010
DOI: 10.1177/112070001002000423
|View full text |Cite
|
Sign up to set email alerts
|

Patient Compliance with Extended Low Molecular Weight Heparin Injections following Hip and Knee Arthroplasty

Abstract: The use of extended duration thromboprophylaxis following hip and knee arthroplasty is becoming widespread. The aim of our study was to determine patient compliance with extended duration thromboprophylaxis using low molecular weight (LMWH) injections following hip and knee arthroplasty. 42 consecutive patients undergoing hip and knee arthroplasty were prospectively contacted during their fifth post operative week. A fully anonymised questionnaire was completed by each patient. All patients responded. One was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Previous studies that have examined TKA and THA patients’ home compliance with DVT prophylaxis found 88-90% 10,11,20 of patients adhered to their medication regimens. Studies examining the compliance of patients at high risk for DVTs demonstrated similar compliance patterns.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies that have examined TKA and THA patients’ home compliance with DVT prophylaxis found 88-90% 10,11,20 of patients adhered to their medication regimens. Studies examining the compliance of patients at high risk for DVTs demonstrated similar compliance patterns.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding reasons of noncompliance, the literature demonstrates that most patients forget to take 1-2 doses, 11 have difficulty purchasing the medication, lack proper instructions or lack someone available to administer the injection. 10 The literature characterizes patients who are compliant to be younger, employed and with a higher degree of education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample size calculation was informed by published data on nonadherence. Non-adherence for injected LMWH as VTE prophylaxis has been reported to range from 10% to 46% 5,7,9,10,15 and from 2% to 52% for oral prophylaxis. 9,10,12,[16][17][18] Based on these figures and on the hypothesis that non-adherence for aspirin would be lower, the sample size calculation used an expected non-adherence of 30% in the enoxaparin group and 15% in the aspirin group, a power of 80% and level of significance of 0.05, yielding a total sample size of 240 patients.…”
Section: Methodsmentioning
confidence: 99%